3D printed anisotropic dielectric composite with meta-material features. (5th March 2016) - Isakov, D.V.; Lei, Q.; Castles, F.; Stevens, C.J.; Grovenor, C.R.M.; Grant, P.S.
Abstract: This paper presents all-dielectric materials used to 3D print coupons with spatially varying dielectric permittivity and possessing high dielectric anisotropy. The coupons were directly printed through a dual-filament fused deposition modelling technique utilizing bespoke feedstock filament comprised a polymer-based micro-ceramic composite with controlled permittivity and loss. By designing the arrangement of both high and low permittivity filament materials in the printed coupons, the microwave operating frequency and magnitude of Mie-type resonances could be manipulated to provide metamaterial-like characteristics. Graphical abstract: Highlights: Filaments with high dielectric permittivity were fabricated 3D structure with anisotropy of permittivity and metamaterial features was printed.